2005
DOI: 10.1038/sj.ejhg.5201356
|View full text |Cite
|
Sign up to set email alerts
|

A family-based association study does not support DYX1C1 on 15q21.3 as a candidate gene in developmental dyslexia

Abstract: We applied a family-based association approach to investigate the role of the DYX1C1 gene on chromosome 15q as a candidate gene for developmental dyslexia (DD) to 158 families containing at least one dyslexic child. We directly sequenced exons 2 and 10 of the DYX1C1 gene and found eight single nucleotide polymorphism (SNPs), three of which (À3G4A, 1249 G4T, 1259 C4G) were suitable for the genetic analyses. We performed single-and multimarker association analyses with DD as a categorical trait by FBAT version 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 34 publications
1
76
2
1
Order By: Relevance
“…The two-SNP haplotype (rs61761345 and rs3743205) shown by Taipale et al 1 to influence dyslexia and confirmed by Marino et al 30 for shortmemory measures (but not for dyslexia 37 ) was tested with Mendel. We observed similar haplotype Figure 1 The location of the single-nucleotide polymorphisms (SNPs) tested across the 84-kb region of DYX1C1.…”
Section: Descriptivementioning
confidence: 85%
See 1 more Smart Citation
“…The two-SNP haplotype (rs61761345 and rs3743205) shown by Taipale et al 1 to influence dyslexia and confirmed by Marino et al 30 for shortmemory measures (but not for dyslexia 37 ) was tested with Mendel. We observed similar haplotype Figure 1 The location of the single-nucleotide polymorphisms (SNPs) tested across the 84-kb region of DYX1C1.…”
Section: Descriptivementioning
confidence: 85%
“…Studies therefore turned to genes in nearby regions, 35 although no candidates have been identified to date, 36 and to the analyses of a small number of additional SNPs in DYX1C1, again without success to date. 37 Thus, although DYX1C1 may be a susceptibility gene for developmental dyslexia, the causal alleles are unknown. Here, we report the first study examining the association of polymorphisms in DYX1C1 with normal variation in reading, examining association at the 2 coding SNPs reported by Taipale et al, 1 and 11 additional tagging SNPs in DYX1C1.…”
Section: Introductionmentioning
confidence: 99%
“…It is also expressed in human glial and neuronal cells but its function is not known. However, this result is not replicated in a twin cohort and a family-based association study by other investigators (Marino et al 2005;Meng et al 2005a;Bellini et al 2005). To resolve this discrepancy, either more studies are needed or this discrepancy could be due to genetic heterogeneity of dyslexia in different populations.…”
Section: Geneticsmentioning
confidence: 88%
“…In this case, the q11 portion of chromosome 15, which had already been identified by linkage analysis and designated DYX1, was translocated onto chromosome 2, and the q21 portion of chromosome 2 was translocated onto chromosome 15 (notated t(2;15)(q11;q21)); analysis of the exact position of the chromosome 15 breakpoint showed that it lay within a previously described gene called EKN1. A small genetic study of families in Finland showed association with EKN1/ DYX1C1 (Taipale et al, 2003), as did a study in Canada (Wigg et al, 2004), but studies in the United States (Meng et al, 2005a) and Italy (Marino et al, 2005) failed to show an association. This implies that the importance of DYX1C1 as a susceptibility gene for RD may be limited to specific populations.…”
Section: Dyx1c1mentioning
confidence: 84%